Economic modeling to evaluate the impact of chronic myeloid leukemia therapy management on the oncology care model in the US. (2nd November 2019) - Jabbour, Elias J.; Mendiola, Martin F.; Lingohr-Smith, Melissa; Lin, Jay; Makenbaeva, Dinara
Abstract: Objective: To develop an economic model to evaluate changes in healthcare costs driven by restricting usage of branded tyrosine kinase inhibitors (TKIs) through substitution with generic imatinib among chronic myeloid leukemia (CML) patients in a typical Oncology Care Model (OCM) practice, and examine the impact on Performance-Based Payment (PBP) eligibility. Methods: An Excel-based economic model of an OCM practice with 1, 000 cancer patients during a 6-month episode of care was developed. Cancer types and proportions of patients treated in the practice were estimated from an OCM report. All-cause healthcare costs were obtained from published literature. It was assumed that if a practice restricts usage of branded TKIs for newly-diagnosed CML patients, 80% of the market share of branded imatinib and 50% of the market shares of 2 nd -gen TKIs would shift to generic imatinib. Among established TKI-treated patients, it was assumed that 80% of the market share of branded imatinib and no patients treated with 2 nd -gen TKIs would shift to the generic. Results: Four CML patients were estimated for a 1, 000-cancer patient OCM practice with a total baseline healthcare cost of 51, 345, 812 during a 6-month episode. If the practice restricts usage of branded TKIs, the shift from 2 nd -gen TKIs to generic imatinib would reduce costs by 12, 970, while shifting from branded to generic imatinib lowers costs by 25, 250 during a 6-month episode. Minimum reductions of 3, 013, 832 in a one-sided risk model and 2, 372, 010 in a two-sided risk model are required for PBP eligibility; the shift from 2 nd -gen TKIs to generic imatinib would account for 0.4% and 0.5% of the savings required for a PBP, respectively. Conclusions: This analysis indicates that the potential cost reduction associated with restricting branded TKI usage among CML patients in an OCM setting will represent only a small proportion of the cost reduction needed for PBP eligibility.